2022
DOI: 10.3389/fnagi.2022.1010765
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive tasks propagate the neural entrainment in response to a visual 40 Hz stimulation in humans

Abstract: IntroductionAlzheimer's disease is one of the great challenges in the coming decades, and despite great efforts, a widely effective disease-modifying therapy in humans remains elusive. One particular promising non-pharmacological therapy that has received increased attention in recent years is based on the Gamma ENtrainment Using Sensory stimulation (GENUS), a high-frequency neural response elicited by a visual and/or auditory stimulus at 40 Hz. While this has shown to be effective in animal models, studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In an elegant experiment, Zhang et al showed appropriate ipsilateral cortical responses to 40 Hz light flicker when participants' left or right eye was blocked from light stimulation [27]. Intracranial EEG (iEEG) recordings also show induced neural activity in superficial as well as deep brain structures when participants were stimulated with 40 Hz light [28] or synchronized 40 Hz light and sound [29]. In both these studies, iEEG leads were surgically placed in patients with medically intractable epilepsy for surgical planning purposes.…”
Section: Feasibility and Optimization Of Gamma Sensory Stimulation Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…In an elegant experiment, Zhang et al showed appropriate ipsilateral cortical responses to 40 Hz light flicker when participants' left or right eye was blocked from light stimulation [27]. Intracranial EEG (iEEG) recordings also show induced neural activity in superficial as well as deep brain structures when participants were stimulated with 40 Hz light [28] or synchronized 40 Hz light and sound [29]. In both these studies, iEEG leads were surgically placed in patients with medically intractable epilepsy for surgical planning purposes.…”
Section: Feasibility and Optimization Of Gamma Sensory Stimulation Fo...mentioning
confidence: 99%
“…Subcortical areas of the brain affected in AD-such as the hippocampus, gyrus rectus, posterior insula, and amygdala-are of particular interest and were found to have induced 40 Hz brain activity during synchronized 40 Hz light and sound stimulation [29]. Furthermore, Khachatryan et al reported that the addition of a visual attention task seemed to increase bilateral hippocampal gamma activity on iEEG during 40 Hz light flicker [28]. Neither study showed any indication that the gamma sensory stimulation (also referred to as Gamma ENtrainment Using Sensory stimulation, GENUS) triggered any epileptiform activity, even in these patients with medically intractable epilepsy.…”
Section: Feasibility and Optimization Of Gamma Sensory Stimulation Fo...mentioning
confidence: 99%
“…For instance, Lee et al (2021) showed that lights flickering at 34 to 38 Hz entrained gamma oscillations stronger than flickering at 40 to 50 Hz in young adults, whereas 32 or 34 Hz light flickering induces stronger gamma entrainment than 38 or 40 Hz flickering in older adults (Park et al, 2022). Further, Khachatryan et al (2022) found that the inclusion of a cognitive task during the GENUS session exerts positive effects on the strength and extent of gamma oscillations, promoting the propagation of gamma entrainment to deep brain areas. Similar methodological investigations on gamma-tACS effectiveness for gamma entrainment have not been conducted in AD patients yet.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a case series report showed that the long-term use of multisensory gamma stimulation over 1 year contributed to the maintenance of cognitive function and increased mood in patients with MCI or AD [ 73 ]. Daily noninvasive gamma frequency sensory stimulation using light or sound was well tolerated, and compliance was equally high in both the control and active group [ 72 , 74 ]. Thus, sensory and multisensory stimulation using the gamma frequency may be a promising approach for treating AD.…”
Section: Discussionmentioning
confidence: 99%